EVALUATION OF PROFITABILITY OF THE BANKING SECTOR OF THE UKRAINE’S ECONOMY - Боярко, Ірина; Голуб, Роксолана (Socio-economic relations in the digital society, 2019)
The article shows the results of an analysis of the domestic banking sector profi tability, performed using the decomposition analysis of equity, and the Du Pont model. Th e infl uence of indicators of net profi t margin, coefficient of return on assets, a multiplier of capital was determined. In addition, net-interest margin indicators and net-spread were subject to research too. Taking into account the fi nancial result of the activity of the domestic banking sector over the past 4 years, banks are losing money, limiting their own profi t opportunities because of poor quality of banks’ loan portfolios. With such realities, the strategic goal of any bank’s activity is to determine a level of profi tability that, firstly, ensures an adequate balance in a rapidly changing market environment and, secondly, that would characterize by an optimal level of risk. Based on the results of the analysis we come to the following conclusions. Firstly, only a group of banks with domestic private capital in 2017 had suffi cient profi tability, simultaneously the banking sector and other groups of banks were unprofi table. Secondly, for all groups of banks, the high value of MK is characteristic, it indicates the formation by banks of a risky structure of the banking balance (the ratio of own and attracted resources) in the direction of achieving an appropriate level of profi tability. Th irdly, a tendency of reducing the return on assets has been revealed both for the banking sector and for groups of banks, that is a consequence of decreasing in the volume of interest-bearing assets, incl. their shares in total assets. Fourthly, the banking sector and all groups of banks have a positive net interest margin and loss-making activities related to the enormous assets provisions and administrative expenses. Fifthly, for the banking sector and various groups of banks, the high value of the net spread is typical, which accompanied by inadequate interest rate policy and risky lending. However, it should be noted the gradual recovery of domestic banks during 2017. Many banks (mostly small ones) are profi table, and large banks are trying to restore their activities through restructuring of bad debts, optimal interest rate policy, eff ective asset and liability management, and corporate governance.